Islam, Civil Society, and Social Work: Muslim Voluntary Welfare Associations in Jordan between Patronage and Empowerment by Egbert Harmsen (Amsterdam: Amsterdam University Press, 2008. 504 pages.) (American Journal of Islam and Society, 2009)
The practice of charity, which is commonly voluntary by definition, is embeddedwithin religious institutions or communities to support their vision ofsocial welfare. In this book, Egbert Harmsen underlines some improvements,advantages, and weaknesses as well as varieties of the roles played byMuslim-based voluntary organizations in the Middle East in general, and inJordan in particular. He reexamines whether such civic values as voluntary,autonomous, egalitarian, community-based initiatives, self-reliance, and independenceunder which civil society organizations developed can impact Muslimsociety on a larger scope.The author reassesses previous research findings, particularly thosepresented by such observers as Janine Clark and Sami Zubaida. Clark’sobservation of (horizontal) networks embedded among middle-classMuslims reveal that the lower class (the poor) does not benefit very muchfrom the existing social institutions. Meanwhile, Zubaida’s scrutiny of the(vertical) relation between Muslim associations and their needy clientsshows that the resulting relationships are generally paternalistic. In responseto Clark’s argument, Harmsen points out that while the social institutionsset up by the middle class do serve middle-class families, they by no means ...